Interest rate pass-through in Turkey during the period of unconventional interest rate corridor - Sahin, Sercin; Cicek, Serkan (AMER INST MATHEMATICAL SCIENCES-AIMS, 2018)
After adopting new monetary policy framework at the end of 2010, the Central Bank of the Republic of Turkey (CBRT) started actively using both multiple short-term policy rates and funding composition over the banks in order to manage the liquidity requirement of the banking system. In this regard, this paper examines interest rate pass-through from multiple policy rates to the retail rates in Turkey and explores asymmetries in the adjustment process within the framework of an asymmetric ARDL model developed by Shin et al. (2014). Our findings revealed that both the CBRT average funding rate and interbank repo rate play an important role rather than official policy rates (weekly repo rate, overnight lending rate, overnight borrowing rate, and late liquidity rate) in this new policy framework. Our results also captured greater pass-through to the interest rate of commercial loans than the interest rate of consumer loans and banking deposits. Moreover, all retail rates respond faster to policy rate cuts than hikes, indicating that the banks were reluctant to raise interest rates than to decrease during the period under investigation.
Keywords: asymmetry; interest rate pass-through; non-linear autoregressive distributed lag; MONETARY-POLICY; ASYMMETRIC ADJUSTMENT; FINANCIAL CRISIS; EASTERN-EUROPE; TRANSMISSION; US; COMPETITION; BANKING; AREA; UK; Business & Economics